Examining Factors Influencing the Smart Farming through AFVC and SFT: Indian Perspectives and Contexts - Gitansh Sardana, K. Rangarajan (Journal of Informatics Education and Research, 2024)
Agriculture is the backbone of Indian economy. It is the lifeline of rural India. The majority of the sectors such as education, automobile, real estate, insurance, banking, information technology, food processing etc. is dependent on the agricultural growth in India in a particular year. It has also major contribution in providing employment for more than 60% of total population in India. The country has rich heritage and tradition of farming right from Sindhu civilization till date. The Indian agriculture witnessed revolutionary changes in due course of time. However, it couldn’t make satisfactory progress even after 70 years of independence in India. One hand, technology transformed the businesses, societies, institutions and enterprises. On the other hand, agriculture has been struggling for existence instead of growth in India. The increasing number of farmer’s suicides and strikes support the view in this regard. There are various socio-economic, psychological, geographical factors influencing the agriculture in India. The various scientists, tech-experts, research institutions have been proactively working towards improvement, simplification, automation of farming challenges. The term ‘Smart farming’ has gained the momentum. The present article aims to examine the major factors influencing while adopting smart farming. It considers the challenges and opportunities while converting Indian farming from ‘traditional farming’ to ‘smart farming’ within Indian context. Globalization, information and communication technology (ICT), government support, farmer education, farm management, farmers’ awareness/ training program, market updates, networking are some of the factors taken into consideration. The study is significant as it deals with the sustainable agriculture in India. It is an attempt to explore the areas in order to regain the lost glory of Indian farming and ensure food safety across the globe.